(untitled) (Journal of Scientific Research, 2009)
The synthesis, characterization, and theoretical study of two Schiff bases of ligands derived from condensation of sulphoacetamide sodium with 4-methoxy benzaldehyde and salicalaldehyde arereported. Spectroscopic techniques, including IR, UV, 1H NMR, and CHN analysis were used to identify the product. The calculated HOMO is largely localized on the N-benzylideneaniline fragment, while the calculated LUMO of the studied molecule is seen to be substantially localized along the C–C axis of the conjugated system. Keyword: Sulphoacetamide sodium complex; Schiff bases; Sulpha drug; Semi-empirical (PM3) methods. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2589 J. Sci. Res. 1 (3), 563-568 (2009)